(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
The technique and its numerical realization of the hard airdrome coatings specified calculations with the consideration of their interaction with heterogeneous multilayer weak soil half-space is proposed. Numerical simulation of the hard airdrome coatings stress-strain state is carried out on the basis of the relations of the elasticity nonlinear theory with the help of the finite element method momentary scheme. The task of calculating the actual concrete coating on a rigid artificial basis of the International Airport "Odesa" runway is solved. A finite-element model for calculating hard surfaces with the use of a momentary finite element scheme and a universal spatial shell finite element has been developed.